Expression of the Components of the Renin–Angiotensin System in Venous Malformation - Siljee, Sam; Keane, Emily; Marsh, Reginald; Brasch, Helen D.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2016)
Background Venous malformation (VM) is the most common form of vascular malformation, consisting of a network of thin-walled ectatic venous channels with deficient or absent media. This study investigated the expression of the components of the renin-angiotensin system (RAS), namely (pro)renin receptor (PRR), angiotensin converting enzyme (ACE), angiotensin II receptor 1 (ATIIR1) and angiotensin II receptor 2 (AIITR2) in subcutaneous (SC) and intramuscular (IM) VM. Materials and Methods SC (n=7) and IM (n=7) VM were analyzed for the expression of PRR, ACE, ATIIR1, and ATIIR2 using 3,3-diaminobenzidine (DAB) and immunofluorescent (IF) immunohistochemical (IHC) staining and NanoString gene expression analysis. Results IHC staining showed expression of PRR, ACE, ATIIR1 and faint expression of ATIIR2 in the endothelium of SC and IM VM. Furthermore, ATIIR2 was expressed by cells away from the endothelium in both SC and IM VM lesions examined. NanoString analysis demonstrated the presence of PRR, ACE and ATIIR1 but not ATIIR2. Conclusions The presence of PRR, ACE, ATIIR1 and potentially ATIIR2, in both SC and IM VM suggests a role for the RAS in the biology of VM. This novel finding may lead to a mechanism-based therapy for VM.